Immediate Cosntituent In English And Indonesian Clauses - Muthmainnah Muthmainnah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2013)
Objective of the study To know immediate cosntituent of English, To know the immedaite constituent of Indonesian. the writer used a descriptive method. This method was used by the reason that the discussion of immediate constituent in English and Indonesian was to represent description about the natural of the facts. Population on serve the all members of research object as the persons, things, animal, etc. With regard to the topic of this study, the population of this study were clauses in English and Indonesian. Sample is part of population. To fulfill the intention of this study, the sample were determined to the simple English and Indonesian clauses which consist of 50 clauses in English and 50 clauses in Indonesian. To collect the data required in this research, the writer used written utterance. The utterance were ib the forms of clauses of English and Indonesian, that have equivalence and standar language.The data being collected were analyzed by using immediate constituent to fulfill the study intent ions as previously mentioned. A box of immediate constituent was used to observer the immediate. Immediate constituent in English, that the first cut is divided into two parts: noun phrase as predicate. Then noun phrase can be formed by pronoun, determiner plus noun. Verb phrase can be formed by verb, modal auxialary plus verb. Immediate constituent in Indonesia, that the first cut is divided into two parts; noun phrase plus verb phrase. Beside, there are other forms of clause, noun phrase plus noun phrase, noun phrase plus adjective phrase. Noun phrase in Indonesia can be formed by pronoun, noun plus noun, or noun plus particle. Verb phrase can be formed by verb, or adverb plus verb